Of Government, Innovation and the Social Sector: An Interview with Ngiam Tong Dow - Ngiam, Tong Dow (Institutional Knowledge at Singapore Management University, 2009)
With homelessness and unemployment looming large in the 1960s, the pioneer public service team turned the situation around within a span of 10 years. Veteran civil servant Ngiam Tong Dow shares his insights from the days of coming nose-to-nose with social breakdown – a time when creative resourcefulness was the only option. Retired and with the benefit of hindsight, he shares with Social Space his thoughts on innovation, government and the way forward for the social sector.